Hepatitis C virus protease inhibitor-resistance mutations: Our experience and review - Wu, Shuang (Baishideng Publishing Group Co., Limited, 2013)
Direct-acting antiviral agents (DAAs) for hepatitis C virus (HCV) infection are one of the major advances in its medical treatment. The HCV protease inhibitors boceprevir and telaprevir were the first approved DAAs in the United States, Europe, and Japan. When combined with peginterferon plus ribavirin, these agents increase sustained virologic response rates to 70%-80% in treatment-naïve patients and previous-treatment relapsers with chronic HCV genotype 1 infection. Without peginterferon plus ribavirin, DAA mono-therapies increased DAA-resistance mutations. Several new DAAs for HCV are now in clinical development and are likely to be approved in the near future. However, it has been reported that the use of these drugs also led to the emergence of DAA-resistance mutations in certain cases. Furthermore, these mutations exhibit cross-resistance to multiple drugs. The prevalence of DAA-resistance mutations in HCV-infected patients who were not treated with DAAs is unknown, and it is as yet uncertain whether such variants are sensitive to DAAs. We performed a population sequence analysis to assess the frequency of such variants in the sera of HCV genotype 1-infected patients not treated with HCV protease inhibitors. Here, we reviewed the literature on resistance variants of HCV protease inhibitors in treatment naïve patients with chronic HCV genotype 1, as well as our experience.